Effects of a recovery swim on subsequent running performance - Lum, D.; Landers, G.; Peeling, P. (International Journal of Sports Medicine, 2010)
The effects of a swimming-based recovery session implemented 10 h post high intensity interval running on subsequent run performance the next day was investigated. Nine well trained triathletes performed two high intensity interval running sessions (HIIS) (8×3 min at 85-90% VO2peak velocity), followed 10 h later by either a swim recovery session (SRS) (20×100 m at 90% of 1 km time trial speed), or a passive recovery session (PRS). Subsequently, a time to fatigue run (TTF) was completed 24 h post-HIIS. Venous blood samples were taken pre-HIIS and pre-TTF to determine the levels of circulating C-Reactive Protein (CRP). Subjects were also asked to rate their perceived recovery prior to commencing the TTF run. The SRS resulted in a significantly longer (830±198 s) TTF as compared to PRS (728±183 s) (p=0.005). There was also a significant percentage change from baseline in the CRP levels 24 h post-HIIS (SRS=-23%, PRS=±5%, p=0.007). There were no significant differences in perceived recovery between two conditions (p=0.40). The findings of the present study showed that a swimming-based recovery session enhanced following day exercise performance, possibly due to the hydrostatic properties of water and its associated influence on inflammation.